Fibrosarcoma pada anjing golden retriever di Rumah Sakit Hewan Pendidikan Universitas Airlangga - Miyayu Soneta Sofyan; Koesnoto Supranianondo; Ira Sari Yudaniayanti; Aisyah Novasari; Endah Paraswati (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2020)
The dog named Agra (Golden Retriever) is suspected of having an axillary tumor. After surgery and examination of the pathology laboratory, it was found that the dog had fibrosarcoma in the axillaries. Fibrosarcoma is a malignant neoplasm that originates from mesenchymal cells, where the dominant cell histology is fibroblast cells that divide excessively and uncontrollably, can attack local tissues, and can move to other locations in the body (metastatic). The histopathological features of fibrosarcoma have fusiform or spindle-shaped cell fascicular growth patterns. The boundary between cells appears unclear with little cytoplasm and collagen fibers form parallel webbing. Grading histology is mainly based on the degree of cellularity, cell differentiation, mitotic features, and the amount of collagen produced by the cell necrosis. Surgery until now is the first and foremost thing in tumor therapy. Benign tumors can be removed with various surgical techniques depending on the location of the tumor. As for malignant tumors, surgery can be carried out by following other additional therapies to inhibit tumor growth.